East Jerusalem from 1967 until the relocation of the US Embassy to it - Mahmoud Tahboub, Naser (Opción, 1970)
Jerusalem file is the most controversial in the Palestinian-Israeli negotiation, which have been repeatedly postponed. This file is being reopened with an attempt to liquidate it when US President Donald Trump announced in 2017 the United States recognition of Jerusalem as the capital of Israel and ordered the planning of the relocation of the U.S. Embassy in Israel from Tel Aviv to Jerusalem, a century after Balfour Declaration of 1917, causing wide international reactions and objections. In this research, we discuss the consequences of Israeli policies, and what comes after the decision of moving the American embassy to Jerusalem ... What are the possibilities? What could happen?